2004
DOI: 10.1007/s10669-004-4801-1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Approaches in Geography and Students? Environmental Attitudes

Abstract: In a study which examines the pattern of geography teaching at the Advanced Level in Hong Kong and assesses the relative effectiveness of didactic and enquiry teaching approaches that are used by the teachers concerned for the development of positive values towards the environment, the question was asked as to whether or not enquiry is more effective than didactic approaches for the development of environmental values, in both the short and long terms, for students as a whole and for students from different ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 31 publications
(35 reference statements)
1
27
0
3
Order By: Relevance
“…According to Yeung (2004), environmental concern (EC) is "an attribute that can represent a person's worries, likes and dislikes about the environment'. Similarly, Kim and Choi (2005), describe EC as "an individual's general orientation toward the environment and an individual's concern level as to environmental issues".…”
Section: Green Human Resource Management and Green Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Yeung (2004), environmental concern (EC) is "an attribute that can represent a person's worries, likes and dislikes about the environment'. Similarly, Kim and Choi (2005), describe EC as "an individual's general orientation toward the environment and an individual's concern level as to environmental issues".…”
Section: Green Human Resource Management and Green Competenciesmentioning
confidence: 99%
“…It is only when an individual is both concerned and worried about the his or her impact on the environment (Yeung, 2004) and generally oriented to positive environmental actions (Kim and Choi, 2005) than such individuals will likely help to prevent environmental degradation and be willing to engage in sustainable green development (Tantawi et al 2009). …”
Section: __________________________mentioning
confidence: 99%
“…Environmental concern is the consumer's emotional immersion with respect to different environmental matters (Lee, 2008). Yeung (2004) has reported that environmental concern denotes several things which are consumer's qualms, uncertainties, likes, dislikes and sympathy when it comes to the environment. Environmental concern is considered a vital variable that affects consumers decision making (Jain & Kaur, 2004), since previous studies established that consumers that are extremely anxious toward the environment are the ones that will take extra measures when purchasing products by calculating and examining how their purchases are likely to affect the environment in some way.…”
Section: Environmental Concernmentioning
confidence: 99%
“…Atributo afetivo que pode representar preocupações, compaixão, gostos e desgostos sobre o meio ambiente (Yeung, 2005).…”
Section: Preocupação Ambientalunclassified